Teaching and learning using the online platform a new experience / Halipah Hamzah and Hazlam Shamin Ahmad Shaberi - Hamzah, Halipah; Ahmad Shaberi, Hazlam Shamin (Universiti Teknologi MARA, 2021)
As a result of the contagion of the viral corona and the implementation of movement control orders, there were changes in various sectors, including the education sector. Students in schools and institutions of higher learning learn from home virtually. Among the online platforms commonly used are Google Meet, Google Classroom, Microsoft Team, Zoom, Webex, Facebook, YouTube, Telegram, WhatsApp, email, and so on. The teaching and learning landscape at Universiti Teknologi MARA (UiTM) is also changing. The online teaching and learning implementation method has taken the place of face-to-face teaching and learning implementation. In this challenging situation, online teaching and learning is considered the best option. Therefore, lecturers need to be prepared with the teaching methods that will be used. They need to be selective in choosing a platform that suits their students’ internet access and capability. Meanwhile, students need to manage their learning wisely. Learning management by students includes planning what to learn as well as reviewing learning materials and references that lecturers have placed on the virtual learning platform.